Space use by South Polar Skua during the breeding season at Svarthammaren, Antarctica - Swärd, Johan Nils (UiT Norges arktiske universitet, 2014)
South Polar Skua is a seabird feeding on both marine resources and on other seabirds’ egg and chicks. There are few studies investigating South Polar Skua space use during breeding season and how it is affected by sex or phenology. This study was carried out during the breeding season 2012-2013 at Svarthammaren in Dronning Maud Land (71° 53′ S, 05° 10′ E). 56 GPS loggers were used to track 48 individuals during incubation and chick rearing period of skua and petrel. At Svarthammaren, South Polar Skua use petrels as their only available food resource with no competitors. We investigated how sex and phenology (skua and petrel incubation and chick rearing periods) affected South Polar Skuas main activities, such as hunting effort (i.e., area used in the petrel colony), time spent on nest defense, and bathing activity. Indeed, petrels defend themselves by spitting oil on their attackers, which affects feathers and flight ability of skua. Skua time budgets depended on prey phenology and differed between sexes. During petrel incubation time, females spent more time around the nest area than males and both skua partners had higher bathing activity during petrel chick-rearing period. Both sexes invested more in hunting effort during the chick-rearing period compared to incubation. The results were mostly in line with previous studies, that skua chick phenology affects their hunting effort and skua had higher bathing activity when they were more exposed for oily attacks. However, we also found that prey phenology affected on skua nest attendance to higher degree than expected, which we believed were based on prey availability.